Pendampingan Pokdarwis untuk Merancang Media Interpretasi Paket Wisata Edukasi Bencana - Shandra Rama Panji Wulung; Hadian, Mohammad Sapari Dwi; Yuliawati, Ayu Krishna; Kikania, Audy Putri; Abdilah, Muhammad Anthesa (LPPPM STAI Darul Hikmah Bangkalan, 2024)
Increasing partner empowerment through knowledge and skills to create added value and increase tourism competitiveness in Cikahuripan Tourism Village requires several efforts. However, efforts to assist in designing interpretation media to support the realization of disaster education tourism packages have the potential to provide solutions. The purpose of this study is to design interpretation media in Cikahuripan Tourism Village, West Bandung Regency. The method uses Participatory Action Research (PAR) on Pokdarwis Tjikahoeripan Gebied as the main partner, which is supported by PT. Katarda Indo Global as an industry partner. Data acquisition through interviews, observation, and documentation to obtain in designing interpretation media for disaster education tourism packages. The data obtained were then analyzed using descriptive qualitative methods and map analysis. The results of the activity showed that interpretation media that can support disaster education tourism packages in Cikahuripan Tourism Village can be in the form of guidebooks, posters, and flyers. Interpretation media contains information about the profile of attractions in Cikahuripan Tourism Village which is equipped with a geotrek route and a map of the distribution of attractions. This activity has implications for tourism village managers in Indonesia, especially tourism villages that are in areas prone to natural disasters.